Outcome of single-stage transanal Swenson pull-through without frozen section in short-segment Hirschsprung’s disease - Khadija-Tul-Kubra; Rashid, Abdul Rehman; Muhammad Amir Hanif (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the outcome of single-stage transanal Swenson pull-through without frozen section in paediatric patients with short-segment Hirschsprung’s disease. Method: The single-group, prospective, cohort study was conducted at the Paediatric Surgical Unit, Nishtar Medical University, Multan, Pakistan, from January 2020 to December 2022 and comprised patients aged 1-12 years who were confirmed to have Hirschsprung’s disease through rectal biopsy and demonstrated short-segment involvement on contrast enema. Single-stage transanal Swenson’s pull-through procedure was performed on all patients without the use of frozen sections. Postoperative follow-up lasted 6 months. Data was analysed using SPSS 25. Results: Of the 97 patients, 64(66%) were boys and 33(34%) were girls. The overall mean age was 2.97±1.62 years. Complications were observed in 21(21.65%) patients, with anastomotic stricture being the most common 6(6.19%), followed by increased stool frequency 5(5.15%), enterocolitis 5(5.15%), and anastomotic leakage 3(3.09%). Biopsy of the excised segment revealed that 2(2.06%) pagtients had aganglionic bowel pull-through. Conclusion: The single-stage transanal pull-through, when performed in the absence of frozen section, was found to be safe in the management of short-segment Hirschsprung’s disease. Key Words: Hirschsprung disease, Swenson pull-through, Transanal pull-through, Anastomotic stenosis, Enterocolitis.